ANALISIS EFEKTIVITAS PENAGIHAN PAJAK MELALUI SURAT TEGURAN, SURAT PAKSA, DAN PENYITAAN PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA CIKARANG UTARA - Simatupang, Delvi Artha; Khairunnisa , Hera; Ekajaya , Tresno (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
Analysis of the Effectiveness of Tax Collection through Warning Letters, Compulsion Letters, to Confiscation at the North Cikarang Pratama Tax Service Office (KPP). Thesis, Faculty of Economics and Business, Jakarta State University, 2025. This study aims to determine the effectiveness of tax collection through warning letters, compulsion letters, to confiscation and the obstacles faced by tax officials in handling tax collection. This study uses a qualitative research type and a field case study approach and uses primary and secondary data. Based on the results of the analysis that has been carried out, it can be concluded that tax collection with warning letters, compulsion letters, to confiscation at the North Cikarang Pratama Tax Service Office from 2021 to 2023 is still relatively ineffective. However, tax collection in 2021 through compulsion letters is relatively effective because of the tax incentives provided by the government due to the occurrence of Covid-19. Ineffective tax collection occurs because taxpayers are not cooperative and do not have good intentions so that taxpayers often avoid implementing tax collection. In addition, the obstacles faced by the tax authorities are the lack of adequate human resources and the occurrence of system errors which cause the amount of arrears that must be collected to not be in accordance with the amount that has been paid.